Hemp Genotype Selection Coefficient to Improve Human Welfare Development (LACCEI, 2024)
Abstract— The new concept of industrial hemp genetic selection examines the relationship levels of the Human Wellbeing Coefficient (K), and the variables grouped in three dimensions of promotion and protection human health with legality framework. The industrial hemp population was 47 hybrids. Eighteen samples were made for each hybrid during six weeks of evaluation. The Hewlett Packard 1100 HPLC equipment was used to analyze the fresh inflorescence samples during the 2019-2020 agricultural season in Montevideo, Uruguay. The hypothesis test, linear regression analysis, ANOVA, Decision Tree, PCA, HCA and Nearest Neighbor Analysis were used as statistics. The coefficient K has a statistically significant positive correlation with the variable Total Cannabidiols -TCBD (CC = ,978 p .005). It also with the Total Tetrahydrocannabinols - TTHC variable (CC = ,936 p .005) and with the Full Protection Projection -R1s variable (CC = ,979 p .005). It is observed that the K coefficient is negatively correlated with the Coefficient of Promotion – R9. When K values increase, the probability of increasing the promotion and protection of human health is higher (R2=0,99 F(4,841) = 30.974.72 Sig = ,000). Hybrids whose K values >4.82 were selected. From the analysis of PCA and HCA, it has been possible to select the six best hybrids and were grouped into two categories. The first group of superior hybrids. This analysis confirmed the potency of the K Coefficient to select hybrids that contain the highest capacity to promote and protect human health.